Riset Eksperimen: Whistleblowing System dan Literasi Tax Audit Terhadap Tindakan Tax Evasion - Supangat, Mahesa Dicky Taruna; Apandi, R. Nelly Nur (Universitas Pendidikan Indonesia, 2022)
AbstractThis research examines specifically about tax evasion action based on tax audit literacy as an internal factor of tax payers and the whistleblowing systemâ€™s condition as a control factor of the tax payers. The research method that used in this research is the experimental method with 2x2 factorial design. This research Â was conducted to undergraduate accounting studies of Indonesia University of Education that were selected using simple random sampling technique. Main hypothesis testing in this research uses Two Way ANOVA. The data that obtained is a tax evasion action in the form of amount of taxable income that will be reported (in percent), where as the result of the decision has previously received treatment of the condition of whistleblowing system and the existence of tax audit literacy. The result of this research in general indicate a decrease in tendency of someone will do the tax evasion. It can be Â achieved if the Directorate General of Taxation provide a good whistleblowing system as a control or the educational institution provide learning about tax audit literacy to their students.